PENGGUNAAN TRICHOKOMPOS UNTUK PENGENDALIAN PENYAKIT LAYU Sclerotium rolfsii (Sacc.) Curzi PADA TANAMAN KACANG TANAH (Arachis hypogaea L.) - Grace Lolyta Simanjuntak; Berty. H. Assa; Jusuf Manueke (Universitas Sam Ratulangi, 2018)
ABSTRACT This study aims to determine the effect of Trichocompost use on the percentage of wilt by S. rolfsii in peanut plants. The study was conducted at the Laboratory of Plant Microbiology and Disease, Sam Ratulangi University Faculty of Agriculture, Manado. The study lasted for three months from March 2019 to June 2019. The study was conducted using a Completely Randomized Design (CRD) with 5 treatments consisting of A = Control / Without Trichocompost, B = 100g Trichocompost, C = 200g Trichocompost, D = 300g Trichocompost, E = 400g Trichocompost. The things observed in this study were the symptoms of the attack, the cause of the disease, and the percentage of plants affected by wilt. Based on the results of the study it can be concluded that Trichocompost able to inhibit the growth of S. rofsii. The dose size of the 400g Trichocompost dose which has the highest ability to inhibit S. rofsii. Keywords: Trichokompost, Peanut plants,Â S. rofsii